Konsep Diri Remaja Panti Sosial Asuhan Anak Tri Murni Padang Panjang - Supriadi, Supriadi; Yusri, Yusri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstractThe concept of self is the view or opinion of a person about himself covering everything he has both physical and psychological. How an individual thinks about his own image and all of his abilities. This study aims to (1) describe the social self-concept of Tri Murni Padang Panjang's childcare institutions, (2) describe the emotional self-concept of adolescents in Tri Murni Padang Panjang childcare institutions, (3) describe the moral self-concept of adolescent orphanage children Tri Murni Padang Panjang, (4) describes the cognitive self-concept of adolescents at Tri Murni Padang Panjang social care institutions. This type of research is quantitative descriptive research. The subjects of this study were Tri Murni Padang Panjang children orphanages. The research subjects were limited to only orphanages in middle and high school with a total of 89 people. The research was carried out by administering questionnaire instruments. Data were analyzed by percentage analysis. The findings of this study show that the results of the self-concept of adolescent orphanages in Tri Murni Padang Panjang are in the good category.The findings of this study show that the results of the self-concept of adolescent orphanages in Tri Murni Padang Panjang are in the good category. more details (1) the social self-concept of adolescents from Tri Murni Padang Panjang social care institutions are in good category, (2) the emotional self-concept of adolescents in Tri Murni Padang Panjang social care institutions are in good category, (3) moral self-concept of orphanage Tri Murni Padang Panjang's childcare is in a very good category, (4) cognitive self-concept of adolescent orphanages Tri Murni Padang Panjang in the good category.Keyword: Self Concept